2016
DOI: 10.1074/jbc.m115.684118
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mouse P2Y6 Nucleotide Receptor Is Associated with Physiological Macrocardia and Amplified Pathological Cardiac Hypertrophy

Abstract: The study of the mechanisms leading to cardiac hypertrophy is essential to better understand cardiac development and regeneration. Pathological conditions such as ischemia or pressure overload can induce a release of extracellular nucleotides within the heart. We recently investigated the potential role of nucleotide P2Y receptors in cardiac development. We showed that adult P2Y 4 -null mice displayed microcardia resulting from defective cardiac angiogenesis. Here we show that loss of another P2Y subtype calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…119 It has been suggested that P2Y 6 receptors could constitute a therapeutic target to regulate cardiac hypertrophy. 120 A 2B receptor activation exerts stronger cardioprotective effects against cardiac ischemia/ reperfusion injury compared with A 2A receptor activation in rats.…”
Section: Heart Diseasesmentioning
confidence: 90%
“…119 It has been suggested that P2Y 6 receptors could constitute a therapeutic target to regulate cardiac hypertrophy. 120 A 2B receptor activation exerts stronger cardioprotective effects against cardiac ischemia/ reperfusion injury compared with A 2A receptor activation in rats.…”
Section: Heart Diseasesmentioning
confidence: 90%
“…Transepithelial Cl -transport across the ciliary epithelium was reported to produce the driving force for aqueous humor formation (45)(46)(47)(48)(49)(50). Cl -secretion from NPE cells is mediated by Cl -channels, whose activity is controlled by intracellular cyclic adenosine monophosphate (cAMP), which is increased by P2Y 6 receptor activation (51,52). It has been reported that cAMP causes both an increase (52-54) and decrease of Cl -secretion (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…P2YR are important therapeutic targets in myocardial protection during ischemia/reperfusion ( Djerada et al, 2017 ). P2Y 6 R could be a therapeutic target to regulate cardiac hypertrophy ( Clouet et al, 2016 ). There is increased expression of P2Y 2 and P2X1R in the hearts of rats with congestive heart failure.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%